Research on fire escape paths for complex public buildings with multiple starting and end points. (5th April 2023) - Zhang, Yi; Wang, Chi; Tong, Wenwen; Liu, Tianqi
In order to solve the path planning problem in the escape and evacuation of dense crowds in complex buildings, an improved Dijkstra's algorithm is proposed in this paper to carry out a research on the planning of the shortest escape path from the starting point of the crowds to the security exit of the building. In order to test the effect of the algorithm, the simulation of the proposed improved algorithm has been carried out in the paper using real commercial bodies as a model with different numbers of people and different distribution densities. The experimental results verify that the proposed algorithm is fast and efficient and can effectively improve the escape efficiency of the crowds, which has strong application value.